Rainfall Forecasting Using Gstar-Sur-Nn Approach in West Java Province - Iriany, Atiek; Firdaus Mahmudi, Wayan; Hadi Nugroho, Waego; Dwi Sulistyono, Agus (International Journal of Engineering and Technology, 2019)
Potato is one of food commodities which is expected to serve as a diversification option of carbohydrate source. One of the negative factors to influence the productivity of potato in the last few years is uncertain climate condition. This problem can be overcome with the development of season forecasting method that produces reliable season forecasting model and has a precise forecasting accuracy, especially in extreme climate conditions. The second year stage of study has reached 70% in completion which includes the implementation of Year I research result, surveying potential locations for potato plants by digging information from farmers and agriculture experts in West Java, the identification of potato crop, identification of factors that influence potato crop growth, identification of rainfall patterns in West Java and exploration of rainfall data of each research rain post. From data exploration and data identification, GSTAR model((1,2,3,4,13,33)(1)â€“Sur is obtained.Â Â